Analysis the geomorphological map and the slope map of the Shiwasor-Akhgler Valley Basin - Ahmed Rasul, Snur; Yassin Ali, Ahmad (Zanco Journal of Human Sciences, 2022)
This research focuses on studying and analyzing the forms and appearances of the earth in the study area, classifying them using satellites image and documenting them in the field through field study for the purpose of drawing a complete geomorphological map of the study area. The creation of a geomorphological map is necessary to evaluate and know the natural resources in the basin as well as to identify and address environmental hazard in the service of various human activities (agriculture, industry, tourism…etc). Geomorphological forms and appearance in any region are a reflection of geomorphological development, tectonic activity, rock composition, process action and geomorphological factors.